Analysis of Service User Perceptions of Services at the Kuala Tungkal Ferry Port - Oktrianti Diani; Siti Nurlaili Triwahyuni; Rizky Amalia (IWTJ : International Water Transport Journal, 2021)
The Kuala Tungkal Ferry Port is located in Tungkal I Village, Tungkal Ilir District, Tanjung Jabung Barat Regency, Jambi Province. Kuala Tungkal Ferry Port is a ferry port organized by the Department of Transportation of West Tanjung Jabung Regency. The Kuala Tungkal Ferry Port serves two routes, namely the pioneering Kuala Tungkal - Dabo Singkep route and the Kuala Tungkal - Telaga Punggur commercial route. Based on the results of the survey in the field, it was found that several services for service users had not been carried out properly, such as the unavailability of evacuation route instructions, evacuation gathering points and emergency telephone numbers, unavailability of port plans/layouts, inappropriate breastfeeding mother room facilities and passenger lane facilities. (gangway) pedestrians and vehicles that have not been separated. This study uses the Customer Statisfaction Index method to determine the level of overall service use satisfaction by looking at the level of importance of service facility instruments, Gap Performance - Importance to determine the gap between service user expectations and perceived service quality and Importance Performance Analysis Quadrant Mapping for to find out the attributes that are the main priorities for improving service quality. Based on the results of the analysis of the Customer Statisfaction Index, the satisfaction index of service users is 69.74% and is included in the satisfied category. Based on the results of the Gap Performance-Importance analysis, the highest gap value is (-1.32) on the attribute of a telephone number sticker for complaints of security disturbances so that passengers can submit complaints about security at the port. Based on the results of the Importance Performance Analysis Quadrant Mapping analysis, there are 7 attributes that are in quadrant I as the main priority for improvement so that the level of satisfaction of service users can increase.